2020
DOI: 10.1186/s12961-019-0506-2
|View full text |Cite
|
Sign up to set email alerts
|

A review of Kenya’s cancer policies to improve access to cancer testing and treatment in the country

Abstract: Background: Cancer is the third-leading cause of mortality in Kenya, resulting in unique challenges to the country's health system. An increase in the number of cancer cases in Kenya over the past decade resulted in legislative actions and policies to guide delivery of cancer services. Kenya's new national cancer control strategy and past policy efforts provide an opportunity to synergise information and enhance understanding to improve cancer diagnosis and treatment in the country. The objectives of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“… 21 24 40–42 Kenya’s health system has focused on efficiency, and the placement of its facilities have been associated with rural–urban disparities in geographical access to primary care services. 22 43 The health system in Malawi has pursued propoor policies, but its level of economic development has hampered efforts to address urban–rural inequities in accessing primary care services for maternal and child health. 23 In the Geo-PSA model, strong Moran’s I correlations between travel time to the closest facility and population density, like those observed in Kenya and Malawi, suggest that the placement of facilities favoured efficiency over equity compared with countries with weaker correlations (Rwanda and Tanzania).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 21 24 40–42 Kenya’s health system has focused on efficiency, and the placement of its facilities have been associated with rural–urban disparities in geographical access to primary care services. 22 43 The health system in Malawi has pursued propoor policies, but its level of economic development has hampered efforts to address urban–rural inequities in accessing primary care services for maternal and child health. 23 In the Geo-PSA model, strong Moran’s I correlations between travel time to the closest facility and population density, like those observed in Kenya and Malawi, suggest that the placement of facilities favoured efficiency over equity compared with countries with weaker correlations (Rwanda and Tanzania).…”
Section: Discussionmentioning
confidence: 99%
“…The countries have also adopted different approaches to implementing government health policies addressed towards achieving equitable health service delivery. [21][22][23][24] Finally, questions regarding tradeoffs between equity and efficiency are particularly pertinent as they expand access to care for cancer and other chronic diseases. [25][26][27] In order to empirically evaluate the association between population density and travel time, we obtained multiple geospatial data inputs described in online supplemental file 1.…”
Section: Study Setting and Geospatial Data Sourcesmentioning
confidence: 99%
“…The noncomprehensive coverage of cancer care by NHIF, as observed at MTRH, has been suggested to contribute to poor outcomes according to a Kenyan qualitative study. 30 In an American registry study, limited access to treatment as a result of inadequate insurance coverage was found to be a contributing factor to lower survival among patients with non–Hodgkin's lymphoma. 31 For Kenyan patients with MM, the current inadequate NHIF coverage, therefore, portends less-than-optimal survival outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the improved diagnosis, treatment and awareness within communities, the burden of cancer continues to rise in the country that is coupled with immense challenges. There is still insufficient general knowledge to the public, pathology and radiology services are weak, with inadequate infrastructure and human resources (Makau-Barasa et al, 2020). Other serious issues surround the affordability and availability of cancer commodities, which impedes access to services by cancer patients.…”
Section: Introductionmentioning
confidence: 99%